RD-Optimisation analysis for H.264/AVC scalable video coding - Issa, Sinzobakwira; Mohammed Jama, Abdi Risaq; Khalifa, Othman Omran (IJCNS, 2010)
The development of multimedia propagations and applications has led to a greater expansion in the field of video transmission over a heterogeneous media as well as iterative delivery platforms with dedicated content requirements. It is known that conventional video coding systems encode video content with given bitrates adapted to a specific function or application. As a result, conventional video coding does not meet the fundamental requirements of the state-of-the-art flexible digital media application. The newly technology based on scalable video coding appears as a new modus operandi that has the ability to satisfy the underlying requirements. In this work, a multi-users scenario was considered for an optimum performance between multiple streams. A rate distortion optimized video frame dropping strategy which can be applied on active network nodes during high traffic intensity was developed. The concept of scalability here, come to introduce the operability of high level of suppleness coding and decoding systems. A base layer which can display the suitable quality of the premium file was considered and take care of the improvement of video quality.